Research on the Phenomenon and Normalisation of the Disorderly Expansion of Capital in the Education and Training Industry - Jiatong Lu (Law and Economy, 2022)
The legitimacy of restricting the disorderly expansion of capital lies in adhering to the public welfare of education. The governance of the disorderly expansion of capital in education and training industry still faces the problems of weak legislation, unclear regulatory authority and responsibility, and unclear bottom line of access to capital. The legislature needs to emphasise the public welfare of education and training in the legislative purpose and integrate the existing norms for special legislation in education and training industry. The competent administrative department needs to clarify the regulatory authority, strengthen the regulatory power, and create a “negative list” for the access to education and training capital.